The USAID Strategic Religious Engagement Summit: What Was Not Said. (1st November 2021) - Karam, Azza
Abstract : This essay reflects on the 2020 USAID Evidence Summit on Strategic Religious Engagement and the field of "religions and development" from the perspective of a practitioner and scholar working in intergovernmental and inter-/multi-religious organizations and spaces for over three decades. Reviewing the papers presented at the Summit, this essay raises some criticisms about perceived gaps in the discussions which also reflect gaps in scholarly work, as well as in some of the ongoing practices, including asking some questions about inclusion of actors, analysis, and narratives not available in English and/or presenting the work of non-Christian resources. The essay ends with some recommendations for working on the religion-and-development nexus going forward.